Assessment of Different Tannin Extracts on Avian Pathogenic Escherichia coli Metabolites Using Nuclear Magnetic Resonance - M Dakheel, Mohammed; A Al-Mnaser, Afnan; J Woodward, Martin; Rymer, Caroline (The Iraqi Journal of Veterinary Medicine, 2023)
Tannins have been demonstrated to inhibit the growth of several chicken illnesses in vitro. The complex compositions of tannins make it difficult for microorganisms to develop bacterial resistance. This study aimed to evaluate the effect of condensed tannins (CT) extracts on metabolic profile of Avian Pathogenic Escherichia coli (APEC) using Nuclear Magnetic Resonance (1H-NMR). The experimental groups were divided into three groups:control (no CT added), high in procyanidins (PC-CT) group, and high in prodelphinidins (PDCT) group, with exposure times of 0, 10, and 24 h. APEC was observed to respond to CT extracted from Tilia flowers (high PC-CT) and black locust leaves (high PD-CT). The levels of amino acids including lysine, leucine, glutamate, phenylalanine, and pyroglutamate were increased with the high PD-CT treatment; however, no significant differences were observed between the PC-CT group and the control. Treatment of APEC culture with high PD-CT also led to a significant decrease in the level of lactate. Thus, high PD-CT affected these metabolisms and could be exploited to control the proliferation of APEC in poultry, thereby improving their health and performance.